2016
DOI: 10.1590/1518-8345.1072.2778
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to immunosuppressive therapy following liver transplantation: an integrative review

Abstract: Objective: to investigate the evidence available in the literature on non-adherence to immunosuppressive therapy among patients undergoing liver transplantation. Method: integrative literature review, including research whose sample consisted of patients aged over 18 years undergoing liver transplantation. It excluded those containing patients undergoing multiple organ transplants. For the selection of articles, Medline / Pubmed, CINAHL, LILACS, Scopus and Embase were searched. The search period corresponded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 32 publications
(44 reference statements)
0
24
0
4
Order By: Relevance
“…Results showing a correlation between fewer daily doses and protective factors for NA are in accordance with other studies. An integrative review (13) compiling risk factors for non-adherence to immunosuppressive medications in adult patients submitted to liver transplantation showed that a decrease in dosage for single daily doses is related to a lower rate of NA, due to adherence difficulties caused by concomitant use of combined medications. As an intervention proposal, we suggested a change in dosage from two daily doses to a single daily dose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results showing a correlation between fewer daily doses and protective factors for NA are in accordance with other studies. An integrative review (13) compiling risk factors for non-adherence to immunosuppressive medications in adult patients submitted to liver transplantation showed that a decrease in dosage for single daily doses is related to a lower rate of NA, due to adherence difficulties caused by concomitant use of combined medications. As an intervention proposal, we suggested a change in dosage from two daily doses to a single daily dose.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a multi-dimension phenomenon determined by the interaction of multiple factors, such as the patient's healthcare system, their socio-economic level, modality of provided treatment, the patient's medical condition, and underlying disease. (13) Patients are considered compliant to pharmaceutical management upon using 80% to 110% of the prescription medication. (14) In the setting of transplantation, NA is estimated to vary from 2% to 67%, with an annual average around 35.6%, (5,10) which results in graft rejection or failure, increased treatment costs, and morbimortality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations